(untitled) (Research, Society and Development, 2022)
Mucoceles are cystic formations that can occur in different topographies in the nasal cavity, especially in the region of the frontal sinus and ethmoid cells, leading to a clinic due to its local compressive effect and presents surgery as the main form of therapeutic management. The objective of this case report is to describe the clinical picture of a young male with a mucocele in the region of posterior ethmoid cells who opened his symptom clinic simulating the findings of an optic neuritis, leading to a clinic of visual loss on the side right. After the initial treatment with corticosteroids did not show clinical results, the imaging exam was able to identify the classic radiological description of a mucocele, transforming the diagnosis and treatment of the patient. In conclusion, it is suggested that the case presented is a reference in the process of building diagnostic hypotheses within a thought in optic neuritis, always raising the need to think about mucocele, and we reiterate that the surgical treatment is the choice in the management of these patients.